Effects of Jaeumkanghwa-tang on tamoxifen responsiveness in preclinical ER+ breast cancer model. Issue 3 (March 2019) - De Oliveira Andrade, Fabia; Yu, Wei; Zhang, Xiyuan; Carney, Elissa; Hu, Rong; Clarke, Robert; FitzGerald, Kevin; Hilakivi-Clarke, Leena
Abstract : Resistance to endocrine therapy remains a clinical challenge in the treatment of estrogen receptor-positive (ER+) breast cancer. We investigated if adding a traditional Asian herbal mixture consisting of 12 herbs, called Jaeumkanghwa-tang (JEKHT), to tamoxifen (TAM) therapy might prevent resistance and recurrence in the ER+ breast cancer model of 7, 12-dimethylbenz[a]anthracene (DMBA)-exposed Sprague–Dawley rats. Rats were divided into four groups treated as follows: 15 mg/kg TAM administered via diet as TAM citrate (TAM only); 500 mg/kg JEKHT administered via drinking water (JEKHT only group); TAM + JEKHT and no treatment control group. The study was replicated using two different batches of JEKHT. In both studies, a significantly higher proportion of ER+ mammary tumors responded to TAM if animals also were treated with JEKHT (experiment 1: 47% vs 65%, P = 0.015; experiment 2: 43% vs 77%, P < 0.001). The risk of local recurrence also was reduced (31% vs 12%, P = 0.002). JEKHT alone was mostly ineffective. In addition, JEKHT prevented the development of premalignant endometrial lesions in TAM-treated rats (20% in TAM only vs 0% in TAM + JEKHT). Co-treatment of antiestrogen-resistant LCC9 human breast cancer cells with 1.6 mg/mL JEKHT reversed their TAM resistance in dose–response studies in vitro . Several traditional herbal medicine preparations can exhibit anti-inflammatory properties and may increase anti-tumor immune activities in the tumor microenvironment. In the tumors of rats treated with both JEKHT and TAM, expression of Il-6 ( P = 0.03), Foxp3 /T regulatory cell (Treg) marker ( P = 0.033) and Tgfβ1 that activates Tregs ( P < 0.001) were significantly downregulated compared with TAM only group. These findings indicate that JEKHT may prevent TAM-induced evasion of tumor immune responses.